2004
DOI: 10.1002/pmic.200300676
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis on structural proteins of Severe Acute Respiratory Syndrome coronavirus

Abstract: Recently, a new coronavirus was isolated from the lung tissue of autopsy sample and nasal/throat swabs of the patients with Severe Acute Respiratory Syndrome (SARS) and the causative association with SARS was determined. To reveal further the characteristics of the virus and to provide insight about the molecular mechanism of SARS etiology, a proteomic strategy was utilized to identify the structural proteins of SARS coronavirus (SARS-CoV) isolated from Vero E6 cells infected with the BJ-01 strain of the virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
71
3
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 36 publications
9
71
3
1
Order By: Relevance
“…The molecular weight shifts after deglycosylation for every S segment in the analysis (Fig. 1B) supported the notion that the SARS-CoV S protein was glycosylated throughout its entire length (7,26).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…The molecular weight shifts after deglycosylation for every S segment in the analysis (Fig. 1B) supported the notion that the SARS-CoV S protein was glycosylated throughout its entire length (7,26).…”
supporting
confidence: 66%
“…It is a large type-I transmembrane glycoprotein containing 23 potential N glycosylation sites (Fig. 1A) (7,26) and is responsible for receptor binding and membrane fusion during virus entry (4,10,11,21,28). The angiotensin-converting enzyme 2 (ACE2) receptor was identified as a receptor for SARS-CoV (10), and a small 193-amino-acid fragment of the S protein (Asn318-Val510) was shown to bind efficiently to ACE2 (24).…”
mentioning
confidence: 99%
“…Western blots (data not shown) showed that only SARS vaccine-immunized ferret sera recognized proteins from SARS-CoV-infected cell lysates corresponding to the molecular masses of N and S proteins (Ying et al, 2004) as well as of purified expressed N and S protein (See et al, 2006).…”
Section: Antibody Responsesmentioning
confidence: 99%
“…were only detectable in 3/4 ferrets and all titres were less than 80. At 7 weeks, the titres were 15-fold higher in ferrets vaccinated with WKV plus alum compared with animals vaccinated with Ad-S/N i.m.Western blots (data not shown) showed that only SARS vaccine-immunized ferret sera recognized proteins from SARS-CoV-infected cell lysates corresponding to the molecular masses of N and S proteins (Ying et al, 2004) as well as of purified expressed N and S protein (See et al, 2006). …”
mentioning
confidence: 99%
“…SARS-CoV is phylogenetically distinct from other characterized coronaviruses [3]. The genome is composed of a relatively conserved region encoding an RNA-dependent RNA polymerase and a variable region containing open reading frames encoding sequences for viral structural proteins: spike (S), envelope (E), membrane (M), and nucleocapsid (N) [4,5]. Like some other coronaviruses, the variable region of SARS-…”
Section: Introductionmentioning
confidence: 99%